Design, synthesis and biological evaluation of novel peptide MC2 analogues from Momordica charantia as potential anti-diabetic agents1. Issue 15 (21st April 2015) - Yang, Baowei; Li, Xue; Zhang, Chenyu; Yan, Sijia; Wei, Wei; Wang, Xuekun; Deng, Xin; Qian, Hai; Lin, Haiyan; Huang, Wenlong
<x xml:space="preserve">Abstract</x> The structure–activity relationship of peptide MC2 resulted in the development of compound III-3, which exhibited potent anti-hyperglycaemic and anti-oxidative effects.